The Evaluation of Nurses’ Practices regarding Electronic Nursing Documentation - Khudhayer, Harith Fathi; Adulwahhab, Musaab Majid (Iraqi National Journal of Nursing Specialties, 2023)
Objective: This study aims to evaluate nurses’ practices regarding electronic nursing documentation Methodology: 40 nurses have been chosen for a pre experimental sample using a non-probability (purposive) method between November 20, 2021, and March 1, 2023. The pretest and posttest comparisons included the same group that had been exposed to the software. Results : table the nurses’ practices toward electronic nursing documentation was described as poor and fair it means that nurses practices need to be improved and developed by an interventional program. there is no significant differences between age, gender and years of employment variables and nurses practices. Conclusions: Between the pretest and posttest, there were notable variations in the interventional program’s efficacy. Thus, the interventional program was successful. Recommendations: An interventional programs and training courses should be provided for nurses to emphasize the practical implementation of the electronic nursing documentation Keywords: interventional program, Electronic nursing documentation.